The Monetary Policy Transmission Mechanism In Indonesia: a Comparative Analysis - Elisa Elisa; Muhammad Subardin; Sri Andaiyani (Universitas Negeri Malang, 2023)
This study analyses a comparison of the role monetary policy transmission mechanism between the interest rate channel and the exchange rate channel in Indonesia for the 2011-2020 period. The type of data is quantitative with secondary data sources, namely the Central Bureau of Statistics and Bank Indonesia. The analytical method used is the Error Correction Model (ECM). The results show that the exchange rate channel is more effective than the interest rate channel because all variables in the exchange rate channel, both in the short and long term, have a significant effect. Exchange rate and inflation variables can give a positive response to economic growth, while net exports and real interest rates give a negative response. The contribution made by the exchange rate channel is 99 percent in the short term and 72.83 percent in the long term. Meanwhile, on the interest rate channel both in the short and long term, the variable deposit rates, real interest rates, inflation, and lending rates have a significant effect on giving a negative response to economic growth. However, loan interest rates are not significant in the short term. Meanwhile, loan interest rates provide a positive response in the long term. The contribution made by the interest rate channel is 65.07 percent in the short term and 86.38 percent in the long term.